(untitled) (Jurnal Teknologi Industri Pertanian, 2026)
The construction of palm oil mills is a complex process influenced by various technical, social, and environmental factors, leading to significant risks, including construction delays, budget overruns, and compromised quality. The sector often neglects to implement effective risk mitigation strategies, resulting in challenges during the planning stage, particularly surrounding structural planning risk and social risk considerations during project approval. This research focuses on the risk management integration within palm oil mill construction at PT HPI, specifically utilizing ISO 31000:2018 and PMBOK during initial planning and design phases. Using a mixed-method approach, data was collected through in-depth interviews and semi-structured questionnaires aimed at experienced professionals in the industry, an analysis of the collected data, through a probability/impact matrix, identified 14 key risk duting the planning stage of palm oil mill project. The three most critical risks highlighted were: 1) Misalignment between project design and intended outcomes, 2) Slow progression in planning caused by unclear data and poorly defined project scope, and 3) delays in necessary bureaucratic approvals. The research indicates that the integration of ISO 31000:2018 with PMBOK facilitates the development of a comprehensive risk management plan. This approach aims to reduce the likelihood of schedule delays, control costs more effectively, and improve the organization’s capability to address social and environmental risks in future palm oil mill projects. Keywords: agroindustry; project risk; planning phase; palm oil mill, risk mitigation